2019
DOI: 10.25159/2415-5829/4202
|View full text |Cite
|
Sign up to set email alerts
|

Societal Perceptions of Breast Cancer among Elderly Women in Nigeria

Abstract: The study examined the impact of the societal perceptions of breast cancer among elderly women on both its care and prevention in south-eastern Nigeria. A representative sample of adult members of the population was drawn in three local government areas in Enugu State. The study drew its rationale from the recognition that the societal perceptions of the causes, nature and management of breast cancer can make a major difference in whether aged women in Nigeria afflicted by breast cancer survive or not. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Recent studies have revealed that the public health institutions played an insignificant role in the management and care of breast cancer among elderly women in Nigeria [20]. According to the study also, 26.1% of the respondents used in the study were of the opinion that most people affected by breast cancer in the state make use of the public health institutions in the state, while 73.9% were of a contrary opinion.…”
Section: Public Health Institutions and Breast Cancer Management In Nmentioning
confidence: 82%
See 4 more Smart Citations
“…Recent studies have revealed that the public health institutions played an insignificant role in the management and care of breast cancer among elderly women in Nigeria [20]. According to the study also, 26.1% of the respondents used in the study were of the opinion that most people affected by breast cancer in the state make use of the public health institutions in the state, while 73.9% were of a contrary opinion.…”
Section: Public Health Institutions and Breast Cancer Management In Nmentioning
confidence: 82%
“…"there is a relationship between income and awareness of breast cancer occurrence among elderly women because most rich people nowadays usually go for routine medical check-ups both within the country and abroad and this creates a lot of awareness on diseases such as breast cancer" [20] The above gained credibility from the opinion of Ashing-Giwa [21] that financial constraints can serve as a barrier to the use of breast cancer preventive and control measures like mammography as women who are living at or below the poverty level have to struggle with competing issues such as food, shelter, safety and employment that take precedence over their own health and well-being. Therefore, given that improved income often results from higher education, this impacts on one's awareness and knowledge generally.…”
Section: Sociocultural Factors In the Management Of Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations